2016
DOI: 10.1371/journal.pone.0153888
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Increases Drought Stress of Juniper Trees in the Mountains of Central Asia

Abstract: Assessments of climate change impacts on forests and their vitality are essential for semi-arid environments such as Central Asia, where the mountain regions belong to the globally important biodiversity hotspots. Alterations in species distribution or drought-induced tree mortality might not only result in a loss of biodiversity but also in a loss of other ecosystem services. Here, we evaluate spatial trends and patterns of the growth-climate relationship in a tree-ring network comprising 33 juniper sites fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
(54 reference statements)
3
30
0
Order By: Relevance
“…The correlations between the regional chronology and the climate factors reveal that the radial growth of the Zeravshan juniper in the low elevation area of Kuramin Range was mainly limited by the water availability. This linkage resembles other findings in the dryland of the inner Asia and suggests the influence of moisture conditions on the juniper growth there [35,37,[46][47][48]. As shown in some studies [22,49], the combination of low precipitation and high temperatures in the previous growing season results in less accumulation of photosynthetic matter for the next year.…”
Section: Climate-growth Relationshipssupporting
confidence: 86%
“…The correlations between the regional chronology and the climate factors reveal that the radial growth of the Zeravshan juniper in the low elevation area of Kuramin Range was mainly limited by the water availability. This linkage resembles other findings in the dryland of the inner Asia and suggests the influence of moisture conditions on the juniper growth there [35,37,[46][47][48]. As shown in some studies [22,49], the combination of low precipitation and high temperatures in the previous growing season results in less accumulation of photosynthetic matter for the next year.…”
Section: Climate-growth Relationshipssupporting
confidence: 86%
“…The relationship between summer mean temperature (SMT) and STD had the strongest correlations; that is, SMT largely corresponded to the annual growth of B. ermanii . This finding consists with the prevailing view that high altitude and latitude treelines are controlled by summer temperatures (Gehrig‐Fasel, Guisan, & Zimmermann, ; Kirdyanov et al., ; Linderholm et al., ; MacDonald, Kremenetski, & Beilman, ; Seim et al., ). We therefore used the STD chronology series to reconstruct the SMT of our transects for the last 160 years (Appendix S4).…”
Section: Methodssupporting
confidence: 77%
“…The tree-ring based reconstructions indicate increased drought stress on conifer tree growth in the mountains of Central Asia. Rapid increase in the rate of warming occurred in the last two decades, which caused the increase of summer aridity [14,17]. Juniper and spruce growing at the lower elevations are most sensitive to the drought stress, while conifers from the upper elevation showed significantly increased response to the temperature trend [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Past tree-ring studies from the Tian Shan Mountains demonstrated strong relationships between climate and spruce and juniper growth, which facilitated reconstructions of summer temperature and moisture variability [14][15][16][17][18]. The tree-ring based reconstructions indicate increased drought stress on conifer tree growth in the mountains of Central Asia.…”
Section: Introductionmentioning
confidence: 99%